Action and activism in selected novels by Ursula K. Le Guin - Deetlefs, Dorothea Maria (Department of English Language and Literature, 2016)
This thesis examines individual and societal action and activism in five science fiction and utopian novels by Ursula K. Le Guin, namely, The left hand of darkness, The word for world is forest, The lathe of heaven, The dispossessed, and Always coming home. Le Guin is a politically committed author whose ideological perspective is informed by feminism, Taoism, and anarchism, as well as a strong ecological awareness. These determine the structure of her fictional societies and the actions of her characters. Each novel is approached on its own terms, with the commentary adhering closely to the text. Individuals and their societies are conceived of as embodying different and conflicting ways of being and doing. The author is seen as an activist by virtue of her political commitment, especially in the case of the self-reflexive, self-critical Always coming home. Included in the Introduction are sections on: Tom Moylan's concept of the critical utopia, which tailors the utopian genre to fit modern views; Le Guin's concept of the yin utopia, one possible form of the critical utopia; and a short section on Taoism, familiarising the reader with concepts and terminology used in the thesis.